RF/FSO Wireless Sensor Networks: A performance study - Sivathasan, S; O'Brien, D; IEEE (2008)
Power consumption is an important design consideration for wireless sensor networks (WSNs). Hybrid radio frequency/free space optical (RF/FSO) WSNs have the potential to reduce this power consumption substantially. This paper studies the performance of the RF/FSO WSN by comparing its network lifetime against the lifetime of a traditional RF-only WSN. Two types of networks are considered: reconfiguring and non-reconfiguring networks. The results show that for the range of network parameters considered, the RF/FSO WSN lasts at least twice as long as its RF-only counterpart. This paper also discusses parameter selection for the best RF/FSO network coverage. © 2008 IEEE.